Implementation of Cyber Counseling for Increase Accessibility of Service Counseling - Juariah, Siti; Abdurrohman, Muhammad Cholid (Lembaga Intelektual Muda (LIM) Maluku, 2026)
In the digital era, the need for easily accessible counseling services is increasing, especially for individuals facing geographic and mobility limitations. This study aims to explore the implementation of cyber counseling as an alternative to increase the accessibility of counseling services. The method used is a literature study by analyzing relevant scientific articles, reports, and academic sources related to cyber counseling and access to mental health services. Data sources were obtained from the Google Scholar database with a publication range of 1988–2024, using the keywords